Current situation and tools for supporting small and medium-sized businesses in Ukraine during martial law. - Holovash, Bohdan; Holovash, Liliia; Verchenko , Valerii (Ways to Improve Construction Efficiency, 2024)
The article analyzes the development trends of micro, small, and medium-sized enterprises (MSMEs) in Ukraine. It examines key trends and the dynamics of new business registrations, assesses changes in the structure of small businesses, and explores their adaptation to modern challenges. Particular attention is given to the problems that hinder business development in Ukraine, along with an overview of domestic government and international donor support programs and tools for entrepreneurial activity. It has been determined that despite significant difficulties, Ukrainian businesses demonstrate high adaptability. Statistical data indicate active growth in the number of registered individual entrepreneurs, reflecting the persistence of entrepreneurial initiative in the country. In 2024, more than 148,000 individual entrepreneurs were registered, which is 10.8% more than in 2023. The highest growth rates are observed in Kyiv, Dnipropetrovsk, and Lviv regions. Among the most promising sectors are trade, transportation, and services. At the same time, small businesses in Ukraine face significant challenges. About 64% of enterprises were forced to completely or partially suspend their activities in the first months of the war. However, by October 2023, 91% of these companies had resumed operations, demonstrating the resilience and flexibility of entrepreneurs in crisis conditions. Key challenges for businesses include difficulties in accessing financing, disruptions in supply chains, limited investment resources, and challenges in restoring production capacities. Special attention is given to the role of government business support programs. The article analyzes the impact of grant initiatives and preferential loans on entrepreneurs' economic activity. Programs such as "eRobota," "Affordable Loans 5-7-9%," and initiatives by international organizations like USAID are examined. These programs help attract financial resources, support startups, and restore business activities in regions most affected by the war. The need for a comprehensive approach to business recovery is substantiated, which includes not only financial support but also improving the regulatory environment, enhancing business conditions, and fostering partnerships between the government, the private sector, and international donors. The study results indicate that further development of entrepreneurship in Ukraine requires an integrated approach, including improving government support tools, promoting business digitalization, and implementing adaptation programs that align Ukrainian businesses with EU business principles and standards, such as the "Circular Economy" and the "European Green Deal."